2020
DOI: 10.1002/jbm.a.37025
|View full text |Cite
|
Sign up to set email alerts
|

Increased yield of gelatin coated therapeutic cells through cholesterol insertion

Abstract: Gelatin coatings are effective in increasing the retention of MSCs injected into the heart and minimizing the damage from acute myocardial infarction (AMI), but early studies suffered from low fractions of the MSCs coated with gelatin. Biotinylation of the MSC surface is a critical first step in the gelatin coating process, and in this study, we evaluated the use of biotinylated cholesterol “lipid insertion” anchors as a substitute for the covalent NHS‐biotin anchors to the cell surface. Streptavidin‐eosin mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…13 Our previous results also demonstrated that gelMA-coated cells have a similar morphology and cell structure to unmodified cells. 13 In addition, we have shown in vitro that gelMA coating did not influence the metabolic activity of coated cells, their immunogenicity or survival. 12 In vivo transplantation of coated cells have also been shown to be safe without a heightened immune response.…”
Section: ■ Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…13 Our previous results also demonstrated that gelMA-coated cells have a similar morphology and cell structure to unmodified cells. 13 In addition, we have shown in vitro that gelMA coating did not influence the metabolic activity of coated cells, their immunogenicity or survival. 12 In vivo transplantation of coated cells have also been shown to be safe without a heightened immune response.…”
Section: ■ Introductionmentioning
confidence: 61%
“…11 Our groups have recently developed a cell surface coating strategy that polymerizes biodegradable gelMA coating on bone marrow cells. 12,13 The presence of cell coating can be detected by flow cytometry or epifluorescence microscopically as demonstrated in our recent publication. 13 Our previous results also demonstrated that gelMA-coated cells have a similar morphology and cell structure to unmodified cells.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These strategies include modifying the properties of MSCs, such as increasing the expression of adhesion factors or inflammatory cytokine receptors, 33 , 34 preconditioning MSCs with toxic elements, exposure to a hypoxia‐ or nutrient‐free environment, 35 , 36 and magnetic targeting techniques. 37 Meanwhile, emerging studies have focused on the encapsulation of MSCs within biomaterials, including injectable hydrogels, 38 , 39 scaffolds, 40 gelatin coatings, 41 and microneedles. 42 Nevertheless, current strategies are limited by the inefficient interactions between implanted cells and excessively inflammatory tissue.…”
Section: Discussionmentioning
confidence: 99%